Neutrophilic urticarial dermatosis: a novel association with poststreptococcal rheumatic disease. (22nd December 2017) - Salam, A.; Papalexopoulou, N.; White, J. M.; Martin, B.; Coakley, G.; McGibbon, D. H.
Summary: Neutrophilic urticarial dermatosis (NUD), a particular clinical and histological entity, can provide a strong pointer to underlying systemic disease, most frequently rheumatological diseases. We report the first case of NUD in association with a post‐streptococcal rheumatic disease, with symptoms including recurrent sore throat, raised antistreptolysin O titre, persistent transient urticaria, polyarthralgia, rheumatic mitral valve disease and Jaccoud arthropathy. Histologically, NUD is characterized by an intense superficial and deep neutrophilic interstitial and perivascular infiltrate, without significant oedema or blood vessel damage. These neutrophils may have a tendency to concentrate along the basement membrane and extend into the epidermis, hair follicles, sebaceous glands and sweat glands (a feature termed 'neutrophilic epitheliotropism'). Clinicians should remain cognizant of NUD, and in particular its frequent association with an underlying inflammatory disorder.